Secoiridoids and triterpenoids from the traditional Tibetan medicine Gentiana veitchiorum and their immunosuppressive activity. (December 2021) - Guo, Kai; Zhou, Ting-Ting; Ren, Xue; Li, Dan; Hu, Hong; Liu, Yan-Chun; Liu, Yan; Li, Sheng-Hong
Abstract: Two undescribed secoiridoids (dehydroxyl-swerimilegenin H and 9-oxo-swerimuslactone A) with eight known ones, and two undescribed triterpenoids [28- O -(3, 4-dihydroxyl-benzyl)-lupeol and 17-hydroperoxide-28-norurs-12-en-3-one] with seven known ones, were isolated from the aerial parts of Gentiana veitchiorum, a traditional Tibetan medicine. The structures of these compounds were elucidated by detailed spectroscopic analyses (including 1D and 2D NMR, HRMS, IR, and specific rotation) and comparison with structurally related known compounds. The isolates were selected to evaluate for their immunosuppressive activity via inhibiting the proliferation of T cells and cytokine IFN-γ production in T cells. Among them, 28- O -(3, 4-dihydroxyl-benzyl)-lupeol exhibited significant effect by inhibiting the proliferation of T cells (IC50, 20.08 μM) and T cell IFN-γ production (IC50, 7.29 μM). Graphical abstract: Two undescribed secoiridoids and two undescribed triterpenoids along with fifteen known analogs were isolated from the aerial parts of Gentiana veitchiorum . Several compounds showed immunosuppressive activity. Image 1 Highlights: Ten secoiridoids and nine triterpenoids were isolated from Gentiana veitchiorum. Two undescribed secoiridoids and two undescribed triterpenoids were discovered. Several compounds showed significant immunosuppressive activity.